2013
DOI: 10.1590/s0100-39842013000400005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of simple liver cysts and hemangiomas in cirrhotic and non-cirrhotic patients submitted to magnetic resonance imaging

Abstract: Objective To determine the prevalence of liver cysts and hemangiomas in the general population and in cirrhotic patients. Materials and Methods Retrospective, observational, and cross-sectional study selecting consecutive magnetic resonance imaging studies performed in the period from February to July 2011. A total of 303 patients (187 women and 116 men) with mean age of 53.3 years were included in the present study. Patients with previously known liver lesions were excluded. The images were consensually analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…However, these data were older than two decades ago which was based exclusively on histopathological findings (autopsies and surgical specimens). According to the more recent study, the prevalence of the hepatic hemangioma in cirrhosis was 8.8% and there was no statistically significant difference with the prevalence in the non-cirrhotic liver [11]. Now with the advancement in both technologies, protocols, better understanding of the histopathology as well as the increasing amont of imaging (CT/MRI), the prevalence of hemangioma is expected to be much higher than previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…However, these data were older than two decades ago which was based exclusively on histopathological findings (autopsies and surgical specimens). According to the more recent study, the prevalence of the hepatic hemangioma in cirrhosis was 8.8% and there was no statistically significant difference with the prevalence in the non-cirrhotic liver [11]. Now with the advancement in both technologies, protocols, better understanding of the histopathology as well as the increasing amont of imaging (CT/MRI), the prevalence of hemangioma is expected to be much higher than previously reported.…”
Section: Discussionmentioning
confidence: 86%
“…The diagnostic performance of MRI in the detection of HCCs of all sizes increases with the utilization of hepatobiliary contrast agents ( 1 , 10 ) . However, in cases of advanced cirrhosis, the contrast uptake by the liver parenchyma may be compromised by decreased hepatocytes function, which would result in reduction of the method's accuracy to detect HCCs ( 4 , 21 ) .…”
Section: Hepatocellular Carcinomamentioning
confidence: 99%
“…With the use of US, CT, and MRI liver cysts are now detected in 2.5 − 5 % of the population [32 -36]. By the use of spiral CT, Carrim et al [37] reported a prevalence of 17.8 %, and by the use of MRI, Galvao et al [38] reported a prevalence of 14.5 %. These results are much closer to post-mortem findings (14 %) [37] than are the results previously reported by Gaines and Samson (2.5 %) [32] by means of ultrasound.…”
Section: Introductionmentioning
confidence: 99%